2019
DOI: 10.1103/physreve.100.032905
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of a grain-scale intruder in a two-dimensional granular medium with and without basal friction

Abstract: We report on a series of experiments in which a grain-sized intruder is pulled by a spring through a 2D granular material comprised of photoelastic disks in a Couette geometry. We study the intruder dynamics as a function of packing fraction for two types of supporting substrates: a frictional glass plate and a layer of water for which basal friction forces are negligible. We observe two dynamical regimes: intermittent flow, in which the intruder moves freely most of the time but occasionally gets stuck, and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In all cases, the dynamics is affected by the packing fraction and the strength of the driving mechanism, whether the intruder is driven at a constant velocity, by a constant force, or by a continually loading spring. An experiment on intruder dynamics in a 2D Couette geometry showed that friction between the particles and the supporting substrate (basal friction) also has a strong effect [15], as had previously been observed only in the context of quasistatic shear-jamming [16].…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…In all cases, the dynamics is affected by the packing fraction and the strength of the driving mechanism, whether the intruder is driven at a constant velocity, by a constant force, or by a continually loading spring. An experiment on intruder dynamics in a 2D Couette geometry showed that friction between the particles and the supporting substrate (basal friction) also has a strong effect [15], as had previously been observed only in the context of quasistatic shear-jamming [16].…”
Section: Introductionmentioning
confidence: 53%
“…The packing fractions used for intruder does get stuck for a short period and then slips. This behavior is reminiscent of clogging of grains that flow through a restricted aperture; we refer to it as intermittent flow dynamics [15]. φ , for the frictional and the frictionless base.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations